Rural ICT policy: Input through data - Koopman, Martine; Mohammed, Mumuni (Technical Centre for Agricultural and Rural Cooperation, 2011)
SEND Foundation Ghana uses open source software and portable computers to gather data on policy implementation from people living in rural communities.